Management accountant’s role and society’s expectations: Sri Lankan study - Shanmugavel Rajeevan (Asian Journal of Accounting Research, 2019)
The purpose of this paper is to gain insights into the gap between management accounting professional’s role and the societal expectations of the management accounting professionals in Sri Lanka.A quantitative research approach was adopted to identify the statistical gap of the management accountant’s role and society’s expectations. Four business sectors were selected from Colombo Stock Exchange as of 31 December 2018. Sample consisted of 160 entities; 480 questionnaires were distributed among three stakeholders (financial accountant/manager, management accountant and human resource manager). Out of the 228 responses received, only 171 responses were usable. Exhibiting an overall response rate of 35.6 per cent.The role expectation of management accountants varies significantly across the selected business sectors in Sri Lanka. There is an increasing demand for contemporary management accounting skills in Sri Lanka.The insights of this study would be of use to policy makers and policy implementers to examine and develop remedial measures to enhance the creditability and transparency of the management accounting profession in Sri Lanka. Academic and professional educational providers can identify future trends and necessary skills of management accounting to improve management accounting curriculum.The evidence from this study contributes to the literature of societal importance of management accounting from a Sri Lankan perspective.